Environmental Related CSR Initiatives for Business Strategy: A Case Study on Small and Medium (SME) Industries in Malaysia - Ahmad, Jamilah; Krishnan, Mahadevan (Springer Nature, 2017)
The practice of social and environmental responsibility is inevitably vital in the present global scenario. Through Corporate Social Responsibility (CSR) also described as social responsibility (SR), companies are able to contribute to sustainable development while contributing to the protection of the natural environment, which can be achieved by the usage of natural resources in a responsible manner. However in most cases, SR has been regarded as a burden to business operations rather than a significant and direct contributor towards business revenue. Being part of the supply chain and catering their products to larger organisations, or, in some cases catering directly to the end customer, Small and Medium Enterprises (SMEs) hold accountability to ensure their products are suited to present demands of various stakeholders. This study aims to understand the perception on environmentally related initiatives among selected manufacturing SMEs and to further understand the obstacles that hinder the manufacturing SMEs towards taking-up strategically inclined environmentally related SR.